Pembuatan Konsentrat Protein Ampas Kelapa (Cocos nucifera L.) Bebas Lemak pada Berbagai Konsentrasi NaOH: Production of Fat-Free Coconut Pulp (Cocos nucifera L.) Protein Concentrates at Various NaOH Concentrations - Ulayya Kasio; Syaiful Bahri; Husain Sosidi; Khairuddin; Ni Ketut Sumarni; Ahmad Ridhay (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2021)
Coconut pulp contains up to 18.2% protein which is one of the wastes from coconut oil processing. Protein from coconut pulp can be used in the manufacture of protein concentrates which are widely used in the food industry. The purpose of this research is to determine the concentration of NaOH that can produce the yield and protein content of coconut pulp protein concentrate. Coconut pulp protein was extracted with NaOH at various concentrations of 0.5, 1, 1.5, 2, and 2.5 M, then continued with salting out using salt (NH4)2SO4 with a saturation of 65%. The crude protein content of coconut pulp protein concentrate was determined by the Kjeldahl method. The results showed that the use of 0.5 M NaOH resulted in the highest protein content of coconut pulp protein concentrate, which was 71.30% with a yield of 14.42%.